2018
DOI: 10.21315/mjms2018.25.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Zerumbone against Paracetamol-Induced Acute Hepatotoxicity in Rats

Abstract: BackgroundZerumbone (ZER) is a major bioactive compound of Zingiber zerumbet, a wild ginger plant that has been documented to have anti-proliferative, anti-inflammatory and anti-oxidant properties. To investigate its hepatoprotective potential, this study was designed to determine the treatment effects of ZER on acute hepatotoxicity induced by paracetamol (PCM) in rats.MethodsThe control group was administered with phosphate buffer solution (PBS) while the other two groups received PCM alone (1000 mg/kg) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…ZER is reported to have pharmacological activity against hepatic disease, including nonalcoholic fatty liver disease, chronic liver fibrosis, and ALI [29,30,31]. However, the underlying mechanism for ALI has not yet been well-studied.…”
Section: Introductionmentioning
confidence: 99%
“…ZER is reported to have pharmacological activity against hepatic disease, including nonalcoholic fatty liver disease, chronic liver fibrosis, and ALI [29,30,31]. However, the underlying mechanism for ALI has not yet been well-studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence showed zerumbone has free radical scavenging activity and attenuates oxidative stress. Recently Z. zerumbet ethyl acetate extract was also documented to have hepatoprotective effects on paracetamol-induced hepatotoxicity in rats and it was believed that the protective effects are due to the presence of high zerumbone composition (Hamid et al 2018). Abdul Hamid et al (2012) also reported that administration of Z. zerumbet ethyl acetate extract protected against paracetamol-induced nephrotoxicity in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Z. zerumbet rhizome, has been consumed as a traditional medicine for many years among Asian population as a cure for fever, stomach ache, sores and also to treat worm infestations (Bhuiyan et al 2009;Somchit & Shukriyah 2003). Pharmacologically, this rhizome also showed high antioxidant activities (Hamid et al 2018) and contained various medicinal values including protection against paracetamol-induced hepatotoxicity (Hamid et al 2011) and nephrotoxicity (Abd Hamid et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers are increasingly keen on herbal products for use in daily health care products or as food supplements. Numerous herbs including Psidium guajava (Alias et al, 2015[ 6 ]), Hibiscus sabdariffa (Akhtar Husin et al, 2017[ 5 ]) and Zingiber zerumbet (Hamid et al, 2018[ 36 ]) were reported to exhibit hepatoprotective effects and high antioxidant activity. Given that current evidence suggesting that cisplatin-induced hepatotoxicity is mediated by oxidative stress (Karadeniz et al, 2011[ 44 ]; Palipoch et al, 2014[ 64 ]); natural products with antioxidant activity could be used as an alternative treatment to overcome this problem.…”
Section: Introductionmentioning
confidence: 99%